Sub-activity Time-Cost Trade-off Model of Building Structural Beam on the Projects in the North Aceh Region - Fachrurrazi Fachrurrazi; Abdullah Abdullah; Yuwaldi Away; Teuku Budi Aulia (Aceh International Journal of Science and Technology, 2019)
Problems for both delayed and accelerated activities in scheduling are common in most projects. This problem can implicate on the additional construction cost with different trends as a specific model. A model can provide valuable information to project acceleration judgement. This research aims to develop the TCTO sub-activity model of formwork, rebar work, and concrete work of the building structural beam on the projects in the North Aceh region. We have collected 33 data sourced from the project cost plan report and respondents judgment in the reviewed area. Descriptive statistics and the regression analysis are used to generate the TCTO model. The results show that the activity duration of the structural beam as broken down into sub-activities of formwork, rebar work and concrete work can be compressed until reaching 40%, 50%, and 40% of its normal duration, respectively. The additional cost of the compressed duration for each sub-activity shows the direct incremental cost per days of 3.67%, 3.63%, and 4.27% of its normal cost. Meanwhile, the possible crash cost of each the sub-activities are 122%, 118.15%, 125.61%, respectively. The models practically represent a linear model in the same daily pattern acceleration.